Chronic complications in patients with type 2 diabetes - Bajkowska-Fiedziukiewicz, Agnieszka; Mikołajczyk-Swatko, Anna; Cypryk, Katarzyna (Menopause Review/Przegląd Menopauzalny, 2009)
Chronic complications often are developing in diabetes. The aim of the present work is the estimation of the frequency of those complications in population of type 2 diabetes patients. 600 patients (319 women and 281 men) were enrolled into the study. At least one complication was diagnosed in 92.2% of the patients; the most frequently found was hypertension. Ischemic heart disease more often occurs in women than in men. In contrast, the peripheral artery disease more often occurs in men. Other complications are equally probable in both genders. Conclusions: Chronic diabetic complications were found in the majority of studied patients, because of that complex therapy should be implemented and many specialists should be engaged.